ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA PEGAWAI STASIUN RADIO PANTAI DISTRIK NAVIGASI KELAS II BANJARMASIN - Rizki Amalia Afriana; Dody Wahyu Widodo (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, Purpose this research is analysis of the high level of absenteeism, low motivation to work, and insufficient number of employees of Radio Navigation District Beach Class II Banjarmasin. Population and sample in this study is the Employee Radio Navigation District Beach Class II Banjarmasin totaling 28 people, they are given some questions about motivation. The method used in this research is descriptive qualitative to describe the administration of employee motivation Navigation District Coastal Radio Station Class II Banjarmasin. The Results from this study showed that the direct motivation in the form of praise, awards, holiday allowances, bonuses and decorations, and the motivation is not directly in the form of equipment and adequate facilities, situation and working environment is needed by employees of district radio stations Navigation Class II Banjarmasin.